2019
DOI: 10.1051/0004-6361/201732206
|View full text |Cite
|
Sign up to set email alerts
|

No surviving non-compact stellar companion to Cassiopeia A

Abstract: Massive stars in binaries can give rise to extreme phenomena such as X-ray binaries and gravitational wave sources after one or both stars end their lives as core-collapse supernovae. Stars in close orbit around a stellar or compact companion are expected to explode as "stripped-envelope supernovae", showing no (Type Ib/c) or little (Type IIb) signs of hydrogen in the spectra, because hydrogen-rich progenitors are too large to fit. The physical processes responsible for the stripping process and the fate of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 81 publications
(125 reference statements)
1
32
0
Order By: Relevance
“…This strategy has been successfully applied to search for runaways by van den Bergh (1980), Guseinov et al (2005), Tetzlaff et al (2013Tetzlaff et al ( , 2014, Dinçel et al (2015), Boubert et al (2017b). Kerzendorf et al (2019) also used the predicted kinematics of disrupted binaries to search for companions of the star that exploded producing the supernova remnant Cas A. Tetzlaff et al (2011) also suggested that, with precise astrometry, it might be possible to relate the ejected companion to the remnant of the companion up to ∼5 Myr after the SN explosion, provided that the compact remnant of the former companion is visible (e.g., as a pulsar).…”
Section: How To Identify Walkaway Starsmentioning
confidence: 99%
“…This strategy has been successfully applied to search for runaways by van den Bergh (1980), Guseinov et al (2005), Tetzlaff et al (2013Tetzlaff et al ( , 2014, Dinçel et al (2015), Boubert et al (2017b). Kerzendorf et al (2019) also used the predicted kinematics of disrupted binaries to search for companions of the star that exploded producing the supernova remnant Cas A. Tetzlaff et al (2011) also suggested that, with precise astrometry, it might be possible to relate the ejected companion to the remnant of the companion up to ∼5 Myr after the SN explosion, provided that the compact remnant of the former companion is visible (e.g., as a pulsar).…”
Section: How To Identify Walkaway Starsmentioning
confidence: 99%
“…In particular the cause of its large mass loss rate is often attributed to a closely interacting binary system. But there is no evidence for a surviving companion star (Kerzendorf et al 2019). Nevertheless, the shock dynamics reported here provide important hints on the late mass-loss history of the progenitor, be it in the form of a partial, asymmetric shell from episodic mass loss, an aspherical cavity created by a brief WR phase wind, or perhaps even a combination of both.…”
Section: Why Did the Reverse Shock Reverse Its Direction?mentioning
confidence: 79%
“…Recent observations have attempted to find this companion that should not be too far from the centre of expansion. However, they instead place extremely strong upper limits on any remaining companion and conclude that there was no stellar companion to the progenitor upon explosion (Kochanek 2018;Kerzendorf et al 2019). Most binary evolution scenarios have been ruled out because of this, and the only remaining channels are binary mergers (Nomoto et al 1995;Lohev et al 2019;Soker 2019), binary disruption after mass transfer from the secondary (Zapartas et al 2017), or the companion is a compact object.…”
Section: Cassiopeia Amentioning
confidence: 99%
“…The inferred ejecta mass is ∼ 2-4 M (Willingale et al 2003;Hwang & Laming 2012), which is typical of a type IIb SN and is consistent with binary progenitor models. However, the upper limits placed on any optical counterpart are so strong that no stellar companion of reasonable mass and age is allowed other than a white dwarf, neutron star or black hole (Kochanek 2018;Kerzendorf et al 2019). Another case is SNR RX J1713.7-3946 (G347.3-0.5), which is inferred to be a type Ib/c SNR (Katsuda et al 2015).…”
Section: Introductionmentioning
confidence: 99%